Benefit of patients with an early and progressed state of hepatocellular carcinoma treated with drug-eluting beads - Rathmann, Nils-Andreas; Sadick, Maliha; Rathmann, Björn; Kostrzewa, Michael; Weiß, Christel; Schönberg, Stefan; Diehl, Steffen J.; Antoni, Christoph Helmer (In vivo, 2016)
Aim: To evaluate drug-eluting beads (DEB) for transarterial chemoembolization (TACE) in patients with Barcelona Clinic Liver Cancer (BCLC) A to D suffering from hepatocellular carcinoma. Material and Methods: The progression-free interval (PFI), survival and laboratory findings of 46 patients were retrospectively analyzed after DEB TACE. Results: The mean survival interval was 16.93 months. The BCLC A/B group had significantly (p=0.01) longer survival compared to C/D: 20.44 and 10.36 months. Mean PFI was 10.75 months with a significantly (p=0.002) longer PFI of the BCLC A/B group (12.71 months) compared to BCLC C/D (3.91 months). In terms of possible adverse events (AEs) significant changes (p<0.05) were observed in cholinesterase, white blood cells, alkaline phosphatase and C-reactive protein. Conclusion: Mean survival and PFI results in the BCLC A/B patient group were comparable to historical controls. In addition, the results suggest that patients with BCLC stage C/D also benefited from DEB TACE.